Novel integration of thermoelectric distiller with direct contact membrane distillation - Diaa Afaneh; Haitham Bahaidarah; Dahiru U. Lawal; Mohamed A. Antar (Energy Conversion and Management: X, 2024)
A thermoelectric distiller (TED) integrated with a direct contact membrane distillation (DCMD) unit was proposed and numerically investigated. The mathematical models of the hybrid TED--–DCMD system were developed and validated. In the proposed hybrid system, the TED provides the heating demand of the DCMD desalination unit in four novel configurations of TED-DCMD integration. The first configuration integrates the TED-DCMD by adding a DCMD heat exchanger coil inside the condensation tank of a TED, while the second configuration involves two TED condensation tanks with each tank containing a DCMD heat exchanger coil. The third configuration also consists of two TED tanks with an external heat exchanger where thermal energy from the TED produced water is transferred to the DCMD feed stream. The fourth configuration is a modification of the second configuration with a thermal recovery from TED produced water for inlet feed water preheating. To investigate the performance (distillate productivity, specific energy consumption, coefficient of performance, and ratio of TED productivity) of each integrated TED-DCMD configuration, the effects of different operating parameters such as DCMD feed flow rate, TEM current, number of TEMs, and TED produced water temperature were examined. Findings indicated that the third configuration is the most energy efficient, with specific energy consumption (SEC) reaching a minimum value of 217 kWh/m3 at low current operation of 2.1 A, and feed flow rate of 4.0 L/min for 8.0 TEMs in the TED. A maximum freshwater productivity and COPh of 2.74 kg/s and 3.24, are attained by the 4th and 3rd configurations, respectively. Results also indicated that elevating the current input encourages higher water productivity. Meanwhile, higher values of SEC and water productivity are attained when operating TED at saturation temperature.